2002
DOI: 10.1107/s0108768102017603
|View full text |Cite
|
Sign up to set email alerts
|

CH3CN: X-ray structural investigation of a unique single crystal. β → α phase transition and crystal structure

Abstract: The phase transition from the low- (beta) to the high-temperature (alpha) form of acetonitrile, CH(3)CN, has been directly observed and studied on a unique single crystal. Both the beta and alpha structures have been determined at temperatures close to the transition temperature (206 K and 201 K), taking advantage of the hysteresis. A single crystal of the beta form was obtained for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(89 citation statements)
references
References 6 publications
3
86
0
Order By: Relevance
“…Furthermore, favorable N-H interactions between molecules in different rows (with N-H distances of 2.52Å and 2.80Å) further stabilize the all-parallel structure. The all-parallel monolayer resembles to some extent the low-temperature (β) phase of solid acetonitrile [38]. From these monolayer calculations we can conclude that acetonitrile matches the structure of the anatase(101) surface very well.…”
Section: Dftmentioning
confidence: 58%
See 1 more Smart Citation
“…Furthermore, favorable N-H interactions between molecules in different rows (with N-H distances of 2.52Å and 2.80Å) further stabilize the all-parallel structure. The all-parallel monolayer resembles to some extent the low-temperature (β) phase of solid acetonitrile [38]. From these monolayer calculations we can conclude that acetonitrile matches the structure of the anatase(101) surface very well.…”
Section: Dftmentioning
confidence: 58%
“…Such antiparallel dimers are also found in the high-temperature (α) phase of solid acetonitrile. [38] The corrugation of the surface is visible in the first solvent and second second layer.…”
Section: Solvent Structure Near the Interfacementioning
confidence: 98%
“…2). [65][66][67][68][69][70][71][72] The low temperature (β or II) and high temperature (α or I) phases both consist of ordered AN molecules. 69 The solid-solid phase transition corresponds to a 90…”
Section: Resultsmentioning
confidence: 99%
“…For example, Natile and coworkers reported that the addition of alcohols to coordinated nitriles to form iminoether complexes of Pt II takes place under basic conditions and that the iminoether ligand initially formed in the Z configuration and subsequently isomerized to the E configuration. [21] Although the Re I acetonitrile complexes we used have a low oxidation state, we discovered that, after the treatment of [Re(CO) 3 [9] are similar to those of the free acetonitrile molecule (1.145 Å) [24] and of the acetonitrile that is coordinated in the fac-{Re(CO) 3 } phosphane complexes. [25,26] However, these phosphane compounds have not been reported to form iminoether compounds, and such coordinated nitriles are not very reactive.…”
Section: Synthesismentioning
confidence: 96%